Exploring Barriers to the Adoption of Digital Technologies for Circular Economy Practices in the Construction Industry in Developing Countries: A Case of Ghana - Pittri, Hayford; Godawatte, Godawatte Arachchige Gimhan Rathnagee; Esangbedo, Osabhie Paul; Antwi-Afari, Prince; Bao, Zhikang (Buildings (Basel), 2025)
Despite the potential of digital transformation to enhance resource efficiency and waste reduction, numerous barriers hinder its adoption. This study examines the critical barriers to digital technology adoption for circular economy implementation in the construction industry in developing countries, using Ghana as a case study. A structured quantitative approach was employed, integrating mean score ranking, exploratory factor analysis, and fuzzy synthetic evaluation to assess the severity of identified barriers. Data were collected from construction professionals through structured surveys, and statistical analyses were performed using SPSS, Excel, and RStudio to determine the criticality of the barriers. The fuzzy synthetic evaluation revealed that financial and adoption constraints emerged as the most critical barrier group, followed closely by institutional and knowledge barriers, while technological and market limitations and regulatory and organizational challenges also exhibited significant impediments. In response, this study develops a strategic framework comprising targeted solutions such as financial incentives, capacity building, regulatory reforms, and technological infrastructure development. This framework addresses not only the barriers but also the associated risks, including financial uncertainty, data security threats, and regulatory gaps. This study contributes to the theoretical understanding of digital technology adoption in CE practices and offers practical recommendations for policymakers, industry stakeholders, and academics seeking to foster sustainable construction practices in the construction industry.